Toxic effects of decabromodiphenyl ether (BDE-209) on human embryonic kidney cells - Li, Min; Liu, Zhenping; Gu, Liang; Yin, Rong; Li, Huarong; Zhang, Xiaobai; Cao, Tongcheng; Jiang, Cizhong (Frontiers in Genetics, 2014)
Polybrominated diphenyl ethers (PBDEs) are widely used as flame-retardant additives in consumer and household products and can escape into the environment over time. PBDEs have become a global environmental organic pollutant due to the properties of persistence, toxicity, and bioaccumulation. The well-studied toxic effects of PBDEs mainly include thyroid hormone disruption and neurotoxicity. There is no consistent conclusions on the carcinogenic potential of PBDEs to date. Here, we explored the toxic effects of BDE-209 on human embryonic kidney cells (HEK293T). The comparison of the gene expression profiles of HEK293T cells with BDE-209 treatment and the negative control found that BDE-209 exposure may alter nucleosome organization through significantly changing the expression of histone gene clusters. The remodeled chromatin structure could further disturb systemic lupus erythematosus as one of the toxic effects of BDE-209. Additionally, gene sets of different cancer modules are positively correlated with BDE-209 exposure. This suggests that BDE-209 has carcinogenic potential for a variety of tumors. Collectively, BDE-209 has a broader toxicity not limited to disruption of thyroid hormone-related biological processes. Notably, the toxic effects of BDE-209 dissolved in dimethyl sulfoxide (DMSO) is not the simply additive effects of BDE-209 and DMSO alone.